2018
DOI: 10.3340/jkns.2017.0203.003
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Increase the Expression of Neural Stem/Progenitor Cells and Improves Functional Recovery after Spinal Cord Injury

Abstract: ObjectiveTo investigates the effect of curcumin on proliferation of spinal cord neural stem/progenitor cells (SC-NSPCs) and functional outcome in a rat spinal cord injury (SCI) model.MethodsSixty adult male Sprague-Dawley rats were randomly and blindly allocated into three groups (sham control group; curcumin treated group after SCI; vehicle treated group after SCI). Functional recovery was evaluated by the Basso, Beattie, and Bresnahan (BBB) scale during 6 weeks after SCI. The expression of SC-NSPC proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…This effect indicates that curcumin exhibits antioxidant activity in wound healing. Studies have evaluated the effect of curcumin on wound healing in rats, and they found that the administration of curcumin enhanced wound healing, improved cell proliferation, and demonstrated an e cient free radical scavenging activity compared with the control and collagen treatments [16,17]. Furthermore, curcumin signi cantly suppresses TNF-αinduced neuroin ammation and the expression levels of IL-6, PGE2, and COX-2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect indicates that curcumin exhibits antioxidant activity in wound healing. Studies have evaluated the effect of curcumin on wound healing in rats, and they found that the administration of curcumin enhanced wound healing, improved cell proliferation, and demonstrated an e cient free radical scavenging activity compared with the control and collagen treatments [16,17]. Furthermore, curcumin signi cantly suppresses TNF-αinduced neuroin ammation and the expression levels of IL-6, PGE2, and COX-2.…”
Section: Resultsmentioning
confidence: 99%
“…This nding may have been caused by the various effects of curcumin. Moreover, curcumin has been found to decrease posttraumatic in ammation owing to its anti-in ammatory properties in experimental spinal cord trauma studies [17,18].…”
Section: Resultsmentioning
confidence: 99%
“…For the prevention of EF progression, the most commonly used and recommended technique that causes less tissue damage is microsurgery (Zavyalov and Pretechikov, 2016). Given that microsurgery leads to less dead space in the efficient free radical scavenging activity compared with the control and collagen treatments (Gopinath et al, 2004;Bang et al, 2018). Furthermore, curcumin significantly suppresses TNF-α-induced neuroinflammation and the expression levels of IL-6, PGE2, and COX-2.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin, which is the active component of turmeric, promotes sensorimotor function recovery via antiin ammation 35 , antioxidant 36 , and anti-apoptosis 37 effects in SCI. There were evidences showed that curcumin improved functional recovery from SCI by combined with the neural stem cells 38,39 or MSCs treatment 40 . The enhanced therapeutic effect was achieved by modulated the proliferation and differentiation of stem cells and alleviated the in ammation microenvironment in the injury region 41 .…”
Section: Discussionmentioning
confidence: 99%